Accounting Factors in Stocks Return: Companies Listed on the Asean Exchange - Farida, Ajeng Luthfiyatul; Fariska, Putri (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The capital market can provide investors, because the selected securities investments are expected to provide a level of return commensurate with the risk the investor bears. The phenomenon that is currently occurring shows that returns are decreasing shares occur in companies in the agricultural companies on the ASEAN, are faced with expectations in the form of investing capital is to obtain a high rate of return low risk. This would be contrary to basic investment principles namely High Risk High Return. Companies listed on the stock exchange are investment commodities with relatively high risk. The nature of investment shares is compassionate and changes to influences originating from within and outside the country, such as changes in politics, economics, government regulations, or modifications within the company or industry. This research aims to determine the factors that influence stock returns, which consist of price book value (PBV), debt-equity ratio (DER), and earnings per share (EPS)—using purposive sampling, with sample 14 agricultural companies listed on the ASEAN Exchange during the 2017-2022 period. Data analysis used multiple linear regression and the hypothesis test using the T-test with a significance level 0.05. The regression analysis results found that only the price book value (PBV) variable had a significant positive effect on stock returns. Meanwhile, the variables debt equity ratio (DER) and earnings per share (EPS) do not affect stock returns simultaneously